Polarized-depolarized Rayleigh scattering for simultaneous composition and temperature measurements in non-isothermal gaseous mixtures - Chakravarthy, K; Le Page, LM; Williams, BAO (Optica Publishing Group, 2023)
This paper demonstrates the application of polarized-depolarized Rayleigh scattering (PDRS) as a simultaneous mixture fraction and temperature diagnostic for non-reacting gaseous mixtures. Previous implementations of this technique have been beneficial when used for combustion and reacting flow applications. This work sought to extend its applicability to non-isothermal mixing of different gases. The use of PDRS shows promise in a range of applications outside combustion, such as in aerodynamic cooling technologies and turbulent heat transfer studies. The general procedure and requirements for applying this diagnostic are elaborated using a proof-of-concept experiment involving gas jet mixing. A numerical sensitivity analysis is then presented, providing insight into the applicability of this technique using different gas combinations and the likely measurement uncertainty. This work demonstrates that appreciable signal-to-noise ratios can be obtained from this diagnostic in gaseous mixtures, yielding simultaneous temperature and mixture fraction visualization, even for an optically non-optimal selection of mixing species.